ANALYSIS EXPOSURE INDEX AS AN OPTIMIZATION EFFORT ON EXAMINATION CHEST POSTERIOR ANTERIOR - Irsal, Muhammad; Syuhada, Firdha Adlia; Ananda, Yolanda Pangestu; Putra, Andre Galih Pratama; Syahputera, Muhammad Rizky; Wibowo, Syahputera; Kahar, Rizky (Journal of Vocational Health Studies, 2020)
Background: Radiographers are responsible for producing image quality which can provide accurate diagnostic information by considering the lowest possible radiation dose according to the As Low As Reasonably Achievable (ALARA) principle. Participation between radiographers and medical physicists is needed in optimizing efforts to control the selection of exposure factors by the required clinical radiographic examination. Purpose: To analyze the exposure index on examination chest posterior-anterior. Method: Quantitative descriptive by analyzing the percentage of exposure index results used in chest PA radiographs as an effort to optimize: image quality and radiation dose indicators on chest PA examinations. Result: Optimization of exposure percentage results of 68%, 25% underexposure, 4% underexposure, 2% overexposure, 1% overexposure (noise). Radiographers have tried to optimize: image quality and image radiation dose by selecting exposure factors that are tailored to the patient's condition and maximizing post-processing for increased quality. Conclusion: In optimizing the CR imaging system, it is necessary to understand exposure index, this is related to the underexposed, optimal, and overexposed categories, besides radiographers can take advantage of post-processing to improve image quality.